Writing exercises to increase coaching transfer: A qualitative study - Fontes, A.; Dello Russo, S. (IWP2020, 2020)
Writing exercises to increase coaching transfer: A qualitative study Research on coaching shows positive effects occur immediately after the intervention. However, the learning and transfer processes are rarely investigated. Our research focuses on a feature of coaching design that could enhance transfer. We explore the role of writing exercises, in between coaching sessions, and how they evoke psychological resources, namely Psychological Capital. We also explore what type of transfer takes place in a field qualitative study involving just over 60 coachees from the same organization